DESIGNING PRACTICAL GRAMMAR MODULE FOR JUNIOR HIGH SCHOOL - Putra, Adhitya Pratama; Sudarsono, Sudarsono; Ikhsanudin, Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
English lessons in public elementary schools in Indonesia have been abolished. Students have problems in making sentences, interpreting and placing some things related to English. In this research researcher used research and development. Researcher used the ADDIE model. This study covered three stages, Analyzing, Designing, and Developing. Researcher chose ten junior high school students and also ten parents from the same students. Researcher used questionnaires, interview sheets, and expert validation sheets as data collection instruments. They argued that grammar was very important in learning English because grammar was the main foundation that will later support English language skills. Based on the result of validity, it showed that the score was categorized 90%, which means that it was good module. Therefore, the product declared no need to be revised (without revision). Module did not need to be revised according to expert and have the potential to increase students'' interest in learning grammar. The students should spend at least an hour studying the module, adjusting to their individual learning styles. Parents should facilitate children in learning so learning can be effective, help students if they find it difficult to understand the material.